2023
DOI: 10.21203/rs.3.rs-2583556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of 24-hour movement behaviours and their associations with mental health in children and adolescents

Abstract: Background. Time-use estimates are typically used to describe 24-hour movement behaviours. However, these behaviours can additionally be characterised by other easily measured metrics. These include sleep quality (e.g., sleep efficiency), 24-hour activity rhythmicity (e.g., between-day rhythm variability), and directly measured acceleration metrics (e.g., intensity gradient). Associations between these characteristics and youth mental health are unclear. This study’s aims were to [1] compare 24-hour movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…Studies that used wrist-worn accelerometers and processing methods such as in the present study have reported comparable times spent in different activities in girls of a similar age. For instance, both Sanders et al [29] and Fairclough et al [30] reported approximately 46 min per day of moderate-to-vigorous physical activity. Fairclough et al [30] also reported similar durations for sleep (7 h), light activity (~270 min), and sedentary behaviours (~620 min) compared to the findings from the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that used wrist-worn accelerometers and processing methods such as in the present study have reported comparable times spent in different activities in girls of a similar age. For instance, both Sanders et al [29] and Fairclough et al [30] reported approximately 46 min per day of moderate-to-vigorous physical activity. Fairclough et al [30] also reported similar durations for sleep (7 h), light activity (~270 min), and sedentary behaviours (~620 min) compared to the findings from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both Sanders et al [29] and Fairclough et al [30] reported approximately 46 min per day of moderate-to-vigorous physical activity. Fairclough et al [30] also reported similar durations for sleep (7 h), light activity (~270 min), and sedentary behaviours (~620 min) compared to the findings from the present study. Current 24 h movement guidelines for children and adolescents aged 5-17 recommend at least 60 min of moderate-to-vigorous physical activity, less than two hours of sedentary screen time, and 8-10 h of sleep for adolescents aged 13-18 each day [23,24].…”
Section: Discussionmentioning
confidence: 99%